High temperature tensile, compression and creep behavior of recycled short carbon fibre reinforced AZ91 magnesium alloy fabricated by a high shearing dispersion technique - Sinan Kandemir; Sarkis Gavras; Hajo Dieringa (Journal of Magnesium and Alloys, 2021)
The present study seeks the feasibility of using short carbon fibres recycled from polymer matrix composites as alternative to virgin carbon fibres in the reinforcement of magnesium alloys. The microstructures, high temperature mechanical and creep properties of AZ91 alloy and its composites with various recycled carbon fibre contents (2.5 and 5 wt.%) and lengths (100 and 500 μm) were investigated in the temperature range of 25–200 °C. The microstructural characterization showed that the high shear dispersion technique provided the cast composites with finer grains and relatively homogenous distribution of fibres. The materials tested displayed different behaviour depending on the type of loading. In general, while enhancements in the mechanical properties of composites is attributed to the load bearing and grain refinement effects of fibres, the fluctuations in the properties were discussed on the basis of porosity formation, relatively high reinforcement content leading to fibre clustering and interlayer found between the matrix and reinforcement compared to those of AZ91 alloy. The compressive creep tests revealed similar or higher minimum creep rates in the recycled carbon fibre reinforced AZ91 in comparison to the unreinforced AZ91.